2008
DOI: 10.1016/j.jmatprotec.2007.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catalysts and post-curing conditions in the polymer network of epoxy and phenolic resins: Preliminary results

Abstract: Abstract:In the earlier study about polymer network of phenolic and epoxies resins mixed with linseed oil, only Phencat 15 was used as the catalyst for the phenolic resin. In this study, Phencat 382 and UH (a urea hydrochloride solution based on a 1 : 1 mole ratio of urea : hydrochloric acid 32%) will be used as catalysts to study their effects on the polymer network of phenolic and epoxy resins mixed with epoxidized linseed oil (ELO) (58%). The effect of each one of these catalysts on the curing and the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…According to Table , 50 wt% modification of ER with ESO increases the per cent elongation by 79.67% while decreases the e‐modulus and hardness. Munoz et al used ELO to modify phenolic‐ and ERs and reported that the strain at the break increased with the modification; however, the flexural modulus decreased with the increasing percentages of ELO in the system . The results of the present study show that elongation of the composites reduces with the increase in the LW content, which is also an indication of the loss in the ductility of the composite.…”
Section: Resultssupporting
confidence: 43%
“…According to Table , 50 wt% modification of ER with ESO increases the per cent elongation by 79.67% while decreases the e‐modulus and hardness. Munoz et al used ELO to modify phenolic‐ and ERs and reported that the strain at the break increased with the modification; however, the flexural modulus decreased with the increasing percentages of ELO in the system . The results of the present study show that elongation of the composites reduces with the increase in the LW content, which is also an indication of the loss in the ductility of the composite.…”
Section: Resultssupporting
confidence: 43%
“…It was noticed that E ′ decreased with the increase in heating treatment temperature first and then increased because of additional crosslinking. In addition, E ′ increased with the increase in aging temperature because of the postcuring of the phenolic resin during thermooxidative aging 23…”
Section: Resultsmentioning
confidence: 99%
“…The curing reaction in UP is a radical polymerization reaction [5]. Resole phenolic resins typically show an exothermic peak at much higher temperature than UP [9,11,12]. The curing of phenolics occurs by polycondensation, producing water and formaldehyde, which evaporate endothermally.…”
Section: Curing and Compatibility Study By Dscmentioning
confidence: 99%